2013
DOI: 10.1007/s11060-013-1233-0
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab for radiation necrosis following treatment of high grade glioma: a systematic review of the literature

Abstract: This review identifies the current literature on the use of bevacizumab for cerebral radiation necrosis in patients with high-grade gliomas, summarizes the clinical course and complications following bevacizumab, and discusses the relative costs and benefits of this therapeutic option. A Medline search was conducted of all clinical studies before September 2012 investigating outcomes following use of bevacizumab therapy for radiation necrosis in patients with high-grade gliomas. Clinical and radiographic outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 28 publications
4
62
1
1
Order By: Relevance
“…Consistent with prior clinical investigations [710], anti-VEGF treated mice show remarkable decreases of RN lesion volume, detected radiographically on both post-contrast T1W and T2W images (Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with prior clinical investigations [710], anti-VEGF treated mice show remarkable decreases of RN lesion volume, detected radiographically on both post-contrast T1W and T2W images (Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
“…Traditional treatments of RN, including corticosteroids and hyperbaric oxygen, are associated with significant toxicity and limited efficacy [23]. Recently, multiple groups have investigated the treatment effect of anti-VEGF antibody (i.e., bevacizumab), which blocks VEGF from reaching its capillary target and is, thus, hypothesized to reduce vascular leakage and associated brain edema, on radiographic volumes of RN clinically [710]. The work presented herein is distinct from prior clinical studies in that the Gamma Knife mouse RN model is a single hemisphere radiation injury model, which allows (i) direct comparisons with the non-irradiated hemisphere and (ii) histological validations that are impractical for clinical cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il n'y a pas de traitement « curatif » de la radionécrose, les corticoïdes à la dose de 1 mg/kg pour une durée d'au moins un mois, la pentoxifylline, le bévacizumab à faible doses (5 mg/kg toutes les trois semaines) [37,38], ainsi que la chirurgie sont les traitements les plus souvent recommandés. Des arbres décisionnels ont même été proposés [30].…”
Section: En Cas D'association De La Radiothérapie Avec Des Médicamentunclassified
“…Patients who are asymptomatic can be observed, while those who are symptomatic are managed with corticosteroids, hyperbaric oxygen therapy (HBOT), bevacizumab, pentoxifylline, vitamin E, laser-induced thermal therapy and/or surgery. [6][7][8][9][10] A recent Cochrane systematic review showed paucity of data on the topic, and was only able to include three comparative studies that used bevacizumab, edaravone and vitamin E. 11 HBOT is a non-invasive treatment that may stabilise necrosis, promote tissue repair and expedite neurological recovery. 12,13 Small retrospective studies have demonstrated high rates of benefit with either rates of stability or improvement estimated at 70%-80% of treated patients.…”
Section: Introductionmentioning
confidence: 99%